Les questions toniques : une forme d’interrogation interpellative - Carole Lailler (Corela)
In the present paper we propose to study the tonic interrogation in French thanks to an “Interactive Grammar”. This grammar is an interpretative and dynamic grammar. It constitutes a direct link between question and answer and assumes that the morphosyntax of interrogation depends on an anticipated answer. We suggest an observation of question-answering corpora coming from the RITEL system showing the distribution of different morphosyntatic kinds of questions. By analyzing from this theoretical standpoint the morphosyntactic variations of interrogations on time, space, and quantity in text corpora, one can notice that tonic questions are certainly rare but that they appear, each time, in a contentious context, close to disruption. Besides the legal acception of the meaning of the verb interpellate, it is thus necessary to underline its energetic and participative dimension. So, we find an opposition between the tonic and periphrastic questions: the anticipated answer does not concern so much the object of the question as the interlocutor himself. He then perceives an obligation of presence in speech, compelling him less to answer than to justify himself and to clarify his attitude.